Ethnographic studies in psychotherapy: A narrative review of methodologies applied in therapeutic practice - Vásquez Carrasco, Eduardo (2025)
Psychotherapy is a complex process that demands a research design capable of capturing its multidimensionality, addressing both relational aspects and the cultural and subjective dynamics involved. In this context, the ethnographic method of qualitative research is positioned as a valuable tool to explore and understand the processes and meanings that emerge around psychotherapeutic practice. This approach allows, through the analysis of the particularities of a specific group, to know and analyze how meanings and narratives are constructed in therapeutic contexts. The main objective of this article is to offer a meta-ethnographic narrative review that synthesizes how ethnographic methodologies have been applied to study various aspects of psychotherapy.